Two-scale modelling of fracture of magnesium phosphate cement under bending using X-ray computed tomography characterisation. (August 2021) - Zhang, Guosheng; Li, Yue; Naderi, Sadjad; Wang, Zigeng; Zhang, Mingzhong
Abstract: This paper presents an efficient experimental-numerical analysis of fracture mechanics in magnesium phosphate cement (MPC) based on the structural and mechanical properties of its constituents including potassium magnesium phosphate hexahydrate (MKP), magnesium oxide (MgO) and pores. At micro-scale, the fracture energy and material strength of solid phases were obtained relying on the combination of nanoindentation experiments and simulation. The X-ray computed tomography (XCT) image-based 3D meso-structure model of MPC beam was generated and incorporated with the finite element cohesive zone model to analyse the fracture process of MPC beam under three-point bending. The unknown fracture parameters of cohesive elements at the interface between MKP and MgO were determined via the model calibration process conditional to the experimental data in terms of relationship between macro-load and crack mouth opening displacement. The cohesive strengths obtained for MKP, MgO and MKP-MgO were found to be 5.8, 106 and 24 MPa, respectively. In the same order, the fracture energies were0.02, 0.08 and 0.04 N/mm, respectively. Graphical abstract: Image 1